2008
DOI: 10.2500/ajr.2008.22.3180
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Biofilm-forming Bacteria in Chronic Rhinosinusitis

Abstract: We show a high percentage of CRS patients (28.6%) whose sinonasal mucopurulence has biofilm-forming capacity. Postsurgical patients had a high prevalence of biofilm-forming bacteria, a possible reflection of the severe nature of their disease. Additional studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
126
1
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(140 citation statements)
references
References 27 publications
5
126
1
8
Order By: Relevance
“…The prevalence of biofilms in CRS patients has been reported to range from 28.6 to 60 % [19,20]. Cryer first detected biofilms in CRS patients by SEM [21].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of biofilms in CRS patients has been reported to range from 28.6 to 60 % [19,20]. Cryer first detected biofilms in CRS patients by SEM [21].…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria primarily exist within biofilms, which are present in 29-72% of CS patients. [38][39][40][41][42][43][44] In eosinophilic disease, these bacteria commonly include Staphylococcus spp. 8,45 These bacteria can drive the recurrent acute infections that plague CS patients, when they transform into their planktonic state and emerge from the biofilm.…”
Section: Sensitization To Colonizing Pathogens Bacteriamentioning
confidence: 99%
“…The expression of these two genes has been observed to be significantly higher in patients with chronic rhinosinusitis (CRS) compared to those without an infection. Another study demonstrated the mRNA and protein expression of TLRs 2, 3, and 4 in the nasal mucosa of patients with intermittent allergic rhinitis [12]- [14]. Furthermore, an increase in the protein expression of all three of these receptors was observed in the nasal mucosa of individuals following an allergen challenge [15].…”
Section: Discussionmentioning
confidence: 99%